Lucky Luke. 6, Ma Dalton - Goscinny, 1926-1977.; Morris, 1923-; Nolan, Frederick (Ashford, Kent [England] : Cinebook, 2007)
Lucky Luke investigates when Ma Dalton, known about Cactus Junction as an eccentric but harmless old woman, suddenly begins robbing banks.
First published: Paris: Dargaud Editeur, c1971.
Spine title.
5.7
3-6.
3-6
Keywords: Cowboys -- Comic books, strips, etc -- Juvenile fiction; Dalton Gang -- Comic books, strips, etc -- Juvenile fiction; Lucky Luke (Fictitious character) -- Comic books, strips, etc -- Juvenile fiction; Cartoons and comics; Cowboys -- Fiction; Dalton Gang -- Fiction; Lucky Luke (Fictitious character) -- Fiction; Western stories; Comic books, strips, etc; Cowhands -- Comic books, strips, etc -- Fiction; Dalton Gang -- Comic books, strips, etc -- Fiction; Lucky Luke (Fictional character) -- Comic books, strips, etc -- Fiction; Western comic books, strips, etc; West (U.S.) -- Comic books, strips, etc -- Juvenile fiction; West (U.S.) -- Fiction; West (U.S.) -- Comic books, strips, etc -- Fiction; Graphic novels; Western comic books, strips, etc